Theatre & human rights - Rae, Paul (Houndmills, Basingstoke, Hampshire, United Kingdom Palgrave Macmillan, 2009)
With its impassioned plays, inspired activism and outspoken artists, the theatre has long provided a venue for promoting and practising human rights. Drawing on a range of international examples, this title examines the challenges presented by the contested relationship between theatre and human rights.
Introduction: against intuition -- The human right to theatre? -- Thinking theatre and human rights -- Theatres of cruelty -- Conclusion: unaccommodated man.
Includes bibliographical references (pages 78-86) and index.
Keywords: Theater -- Political aspects; Human rights